If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + -17 = -13x + 7 + 9x Reorder the terms: -17 + -12x = -13x + 7 + 9x Reorder the terms: -17 + -12x = 7 + -13x + 9x Combine like terms: -13x + 9x = -4x -17 + -12x = 7 + -4x Solving -17 + -12x = 7 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -17 + -12x + 4x = 7 + -4x + 4x Combine like terms: -12x + 4x = -8x -17 + -8x = 7 + -4x + 4x Combine like terms: -4x + 4x = 0 -17 + -8x = 7 + 0 -17 + -8x = 7 Add '17' to each side of the equation. -17 + 17 + -8x = 7 + 17 Combine like terms: -17 + 17 = 0 0 + -8x = 7 + 17 -8x = 7 + 17 Combine like terms: 7 + 17 = 24 -8x = 24 Divide each side by '-8'. x = -3 Simplifying x = -3
| -10x^2-27xy-5y^2=0 | | 7x^2-56x-21=0 | | 0.02(60)+0.04x=0.03(50+x) | | -5x^2+6x+6=0 | | k-3=24 | | -x^2+2x-8=0 | | a+2(4+2a-c)-4c+2=0 | | v+9=U | | 5(7x-3)=-10(-2x+1) | | -6+27+(-70)= | | 5r^2=35r | | 5(f-8)=-40 | | 3x+12=28-5x | | 1-8x=-16x^2 | | 2b-c-a+4=0 | | 3+7lnx=38 | | 2b-a-c+4=0 | | -10(s+5)=-133 | | 2a-b-c+4=0 | | 7+12x=29+x | | -49=-2x+3(-2x+13) | | -10(s+5)=133 | | 54n^3-2000=0 | | -3x^2+6x=4 | | t-(-2)=-8 | | b+2c-4a+2=0 | | b+2a-4c+2=0 | | 4.2/3-1 | | 6(t+2)=0 | | 2(2b+6)=4b-8 | | 7|-1-3|= | | 5-3(3+5x)=71 |